Development and evaluation of a real-time polymerase chain reaction assay for the rapid detection of Talaromyces marneffei MP1 gene in human plasma - Hien, H; Thanh, T; Thu, N; Nguyen, A; Thanh, N; Lan, N; Simmons, C; Shikuma, C; Chau, N; Thwaites, G; Le, T (Blackwell Verlag GmbH, 2016)
Penicilliosis caused by Talaromyces marneffei is a common AIDS-defining illness in South and Southeast Asia. Diagnosis is based on culture which can take up to 14 days for identification, leading to treatment delay and increased mortality. We developed a TaqMan real-time PCR assay targeting the MP1 gene encoding an abundant cell wall protein specific to T. marneffei. The assay's performance was evaluated in MP1-containing plasmids, clinical isolates, and plasma from HIV-infected patients with and without penicilliosis. The assay consistently detected 10 copies of MP1-containing plasmids per reaction and 100 T. marneffei yeast cells per millilitre plasma. There were no amplification with seven other Penicillium species and six other HIV-associated fungal pathogens tested. The assay was evaluated in 70 patients with AIDS: 50 patients with culture-confirmed penicilliosis and 20 patients with opportunistic infections other than penicilliosis. The diagnostic sensitivity was 70.4% (19/27, 95% CI: 51.5-84.1%) and 52.2% (12/23, 95% CI: 33.0-70.8%) in plasma samples collected prior to and within 48 h of antifungal therapy respectively. The diagnostic specificity was 100% (20/20, 95% CI: 83.9-100%). This assay provides a useful tool for the rapid diagnosis of T. marneffei infection and has the potential to improve the management of patients with penicilliosis.